Computational studies of structures and properties of metallaboranes. Part 3: protonated iron bis(dicarbollide), [3-Fe-(1,2-C2B9H11)2H]- - Bühl, Michael; Hnyk, Drahomír; Machacek, Jan (Inorganic chemistry, 2007)
On the basis of the energies and 11B NMR chemical shifts computed at the BP86/AE1(*) and GIAO-B3LYP/II' levels of density functional theory, respectively, the structure of the long-known protonated iron(II) bis(dicarbollide) can be assigned to a staggered isomer with a cisoid conformation of the carborane ligands. In the unprotonated species, in contrast, these ligands adopt the usual trans orientation, suggesting that suitable control of protonation/deprotonation equilibria could induce rotary motion at the molecular level.